Jasmonate Signaling Methods and Protocols - Goossens, Alain; Pauwels, Laurens; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
It is now well established that jasmonates, originally identified as the major component of jasmine scent, play a universal role in the plant kingdom and are involved in the regulation of diverse aspects of plant biology, including growth, development, metabolism, and interaction with the environment.  In Jasmonate Signaling: Methods and Protocols, experts in the field aim to unite powerful emerging omics platforms with a number of key reductionist approaches to form a comprehensive collection of tools and protocols. The detailed chapters in this book embrace physiological, environmental, molecular, omics, and bioinformatics approaches that allow dissecting jasmonate actions in the model species Arabidopsis thaliana or in other plants.  Written in the highly successful Methods in Molecular Biology series format, chapters feature introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, along with tips on troubleshooting and avoiding known pitfalls.   Authoritative and cutting-edge, Jasmonate Signaling: Methods and Protocols will empower interested researchers to dissect all steps of jasmonate signaling and the processes they modulate.
Phenotyping Jasmonate Regulation of Senescence -- Characterizing Jasmonate Regulation of Male Fertility in Arabidopsis -- Phenotyping Jasmonate Regulation of Root Growth -- Bioassays for Assessing Jasmonate-Dependent Defenses Triggered by Pathogens, Herbivorous Insects, or Beneficial Rhizobacteria -- Elicitation of Jasmonate-Mediated Defense Responses by Mechanical Wounding and Insect Herbivory -- Pseudomonas syringae Infection Assays in Arabidopsis -- Jasmonate Signaling in the Field, Part I: Elicited Changes in Jasmonate Pools of Transgenic Nicotiana attenuata Populations -- Jasmonate Signaling in the Field, Part II: Insect-Guided Characterization of Genetic Variations in Jasmonate-Dependent Defenses of Transgenic and Natural Nicotiana attenuata Populations -- Profiling of Jasmonic Acid-Related Metabolites and Hormones in Wounded Leaves -- A Non-Targeted Approach for Extended Liquid Chromatography-Mass Spectrometry Profiling of Free and Esterified Jasmonates After Wounding -- Cell-Specific Detection of Jasmonates by Means of an Immunocytological Approach -- Jasmonic Acid-Amino Acid Conjugation Enzyme Assays -- Pull-Down Analysis of Interactions Among Jasmonic Acid Core Signaling Proteins -- Yeast Two-Hybrid Analysis of Jasmonate Signaling Proteins -- Modified Bimolecular Fluorescence Complementation Assay to Study the Inhibition of Transcription Complex Formation by JAZ Proteins -- Agroinfiltration of Nicotiana benthamiana Leaves for Co-Localization of Regulatory Proteins Involved in Jasmonate Signaling -- Electrophoretic Mobility Shift Assay for the Analysis of Interactions of Jasmonic Acid-Responsive Transcription Factors with DNA -- Transient Expression Assays in Tobacco Protoplasts -- Functional Analysis of Jasmonic Acid-Responsive Secondary Metabolite Transporters -- Expression Analysis of Jasmonate-Responsive Lectins in Plants -- Profiling the Jasmonic Acid Responses by Nuclear Magnetic Resonance-Based Metabolomics -- Metabolite Profiling of Plant Tissues by Liquid Chromatography Fourier Transform Ion Cyclotron Resonance Mass Spectrometry -- cDNA-AFLP-Based Transcript Profiling for Genome-Wide Expression Analysis of Jasmonate-Treated Plants and Plant Cultures -- Analysis of RNA-Seq Data with TopHat and Cufflinks for Genome-Wide Expression Analysis of Jasmonate-Treated Plants and Plant Cultures -- Transcriptome Coexpression Analysis Using ATTED-II for Integrated Transcriptomics/Metabolomics Analysis -- A Guide to CORNET for the Construction of Coexpression and Protein-Protein Interaction Networks.
Keywords: Plant science; Botany; Plant biochemistry; Plant Sciences; Plant Biochemistry